2007
DOI: 10.1093/annonc/mdm005
|View full text |Cite
|
Sign up to set email alerts
|

Maximal neutropenia during chemotherapy and radiotherapy is significantly associated with the development of acute radiation-induced dysphagia in lung cancer patients

Abstract: The maximal neutrophil toxicity during concurrent chemotherapy and radiotherapy is strongly associated with the development of acute dysphagia. A multivariate predictive model was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 26 publications
4
37
1
Order By: Relevance
“…In this series, we confirm that neutropenia is a very important parameter that is associated with the development of severe oesophagitis during or after concurrent chemoradiotherapy [16]. Patients who received sequential chemotherapy and radiotherapy had the same incidence of severe neutropenia during their induction phase as individuals who were treated with concurrent chemoradiation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this series, we confirm that neutropenia is a very important parameter that is associated with the development of severe oesophagitis during or after concurrent chemoradiotherapy [16]. Patients who received sequential chemotherapy and radiotherapy had the same incidence of severe neutropenia during their induction phase as individuals who were treated with concurrent chemoradiation.…”
Section: Discussionsupporting
confidence: 70%
“…In an earlier study, we found that not the dose of chemotherapy was correlated with radiation-induced oesophagitis in concurrent schedules, but the level of neutropenia [16]. Patients with grade 4 neutropenia had an odds ratio of about 20 to develop grade 3 oesophagitis.…”
Section: Is Susceptibility For Neutropenia a Risk Factor?mentioning
confidence: 76%
“…This cannot be straightforwardly explained by a reduction in radiation fields, because both our previous planning study and the present trial showed an equal percentage of increases and decreases in radiation fields when using PET instead of CT. Possible hypotheses include the relatively long SER in the present study (32), a lower than average neutropenia level (33), which was not investigated in the present study, or simply an observation due to chance. If the current finding of lower esophageal toxicity holds true, PET-based SNI could provide opportunities for dose escalation and, hence, improvement of locoregional tumor control.…”
Section: Discussionmentioning
confidence: 82%
“…Note, however, that a model reliably identifying subgroups of patients with, say, a 10% and a 40% risk of toxicity would most likely be clinically useful, but if the latter group is labeled as “responders” there would still be a 60% false positive rate. In this case a binned comparison of observed and expected toxicity may be more informative 35 . Cross validation techniques have been suggested for NTCP modeling 29 but have so far not been widely applied.…”
Section: Model Validation and Data Analysismentioning
confidence: 99%